EL MONASTERIO DE SANTA MARTA. PROCESO DE RESTAURACIÓN Y CONSERVACIÓN DE LA PORTADA DE LA IGLESIA CONVENTUAL DE LA ORDEN DE CLAUSURA DE LAS HERMANAS JERÓNIMAS EN CÓRDOBA, ESPAÑA - Wis Molino, Noema (2017)
In the early days of the 12th century, the fall of the Muslim Empire and capture of Cordoba was taking place in the kingdoms of Spain. The process of Reconquista that began in the south-east of Andalucía, through the province of Jaen, and continued towards the most important city of the ter- ritories of Al Ándalus, Cordoba. A new period in art and history began, influenced by trends of the Kingdom of Castilla, already under the control of Christian kings. In the course of this new stage, a new architectural typology emerged in the city. It had religious purpose and are known as the pal- ace-convents. One of the most important edifices is the Santa Marta convent along with its church, a landmark in late Gothic architecture. It owes such characteristics to families of stonemasons and sculptors who arrived from Burgos, making the city into this magnificent site. The main façade of the church was sculpted and designed in 1511 by Hernán Ruiz I, master of the cathedral (former mosque of the caliphate). This front is the subject of research and restoration work, which revalued this architectonical assortment of the Cordoba of the 16th century.